Pagamento por serviços ambientais como mecanismo colaborador para ações de plano de bacia hidrográfica no Rio Grande do Sul - Panziera, André Gonçalves (2022)
The most strategic instrument of the State Water Resources Policy in RS is the watershed plan. The instrument is used by the watershed committee to manage water resources and associated environmental processes. Over the years, however, failures and functions in the implementation of its actions have already been problematized. Complementing the plan with the committees, proposing payment for environmental services as an alternative, can be a path that helps in the solution. Thus, to propose a methodological sequence to evaluate the use of environmental services as a collaboration mechanism for the implementation of graphic basin plans. The methodological sequence initiated a systematic literature review, using PRISMA to search and protocol global scientific articles. Then, the Iramuteq program was used to process the textual data of the selected articles. With this, different payment mechanisms for environmental services were summarized, culminating in representative ideas of these. Such ideas and choices were drawn up, a list of books and numerical choices were drawn up. At the same time, achievements and known indicators of two others and others were, a while on the level of implementation of scientific management actions, using adapted to the characteristics of the literature. The different method, all the experiments were designed using for different experiments with the methods of the river Quar and Pardo watersheds. The use of the method on the concepts about the visual structure or generate, here and actions of the consensus plan. This was also used to generate consensus on the payment of environmental services, as a total or partial means of carrying out actions or programs of the watershed plan. The results of the literature review, followed by the soil and watershed. As a result, the deadline for resources and the level of implementation of actions were consensually low. Characterization indicators related to environmental services were consensually very low, demonstrating the lack of interest, or misunderstanding of the thematic relationship with watershed management. For the answers in the lack of actions, there is no discrimination of actions, but training answers that we, lack of resources as alternatives to encourage the project. There was a consensus that the representative ideas of PES, together with the participants, can hardly implement the actions of the watershed plan. A diagram was suggested with the addition of information from environmental services for integration in the different phases of the watershed plan. Therefore, there is room to improve actions of hydrographic plans with the use of payment for environmental services. However, the river basin committees need to be able to understand the totality of the existing proposals on payment for environmental services.